Multi-UAV planning and task allocation - Bestaoui Sebbane, Yasmina (Boca Raton : CRC Press, 2020)
Multi-robot systems are a major research topic in robotics. Designing, testing, and deploying aerial robots in the real world is a possibility due to recent technological advances. This book explores different aspects of cooperation in multiagent systems. It covers the team approach as well as deterministic decision-making. It also presents distributed receding horizon control, as well as conflict resolution, artificial potentials, and symbolic planning. The book also covers association with limited communications, as well as genetic algorithms and game theory reasoning. Multiagent decision-making and algorithms for optimal planning are also covered along with case studies. Key features: Provides a comprehensive introduction to multi-robot systems planning and task allocation Explores multi-robot aerial planning; flight planning; orienteering and coverage; and deployment, patrolling, and foraging Includes real-world case studies Treats different aspects of cooperation in multiagent systems Both scientists and practitioners in the field of robotics will find this text valuable.
1.6.2 Expanding Grid Coverage -- 1.6.3 Optimization of Perimeter Patrol Operations -- 1.6.3.1 Multiagent Markov Decision Process -- 1.6.3.2 Anytime Error Minimization Search -- 1.6.4 Stochastic Strategies for Surveillance -- 1.6.4.1 Analysis Methods -- 1.6.4.2 Problems in 1D -- 1.6.4.3 Complete Graphs -- 1.7 Conclusions -- Chapter 2 Flight Planning -- 2.1 Introduction -- 2.2 Path and Trajectory Planning -- 2.2.1 Trim Trajectories -- 2.2.2 Trajectory Planning -- 2.2.2.1 Time Optimal Trajectories -- 2.2.2.2 Nonholonomic Motion Planning -- 2.2.3 Path Planning -- 2.2.3.1 B-Spline Formulation
OCLC-licensed vendor bibliographic record.
Keywords: Drone aircraft -- Automatic control; Multiagent systems; Adaptive control systems; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Machine Theory; COMPUTERS / Neural Networks